Influência dos compostos orgânicos voláteis no potencial de formação do ozônio troposférico na região da Grande Vitória-ES - Galvão, Elson Silva (2014)
In the present study, the ozone forming potential (OFP) from volatile organic compounds (VOCs) in theatmosphereof Metropolitan Region of Grande Vitória(RMGV) has been studied on the periods between02/05/2013 to 04/05/2013 and 05/16/2013 to 06/21/2013. Each species of VOC has a particular reactivity on ozone formingpotential, so the knowledge of these species in the local atmosphere is of great importance in proposing measures to control of air pollution. Passive samplers were installed at three of air quality monitoring stations (RAMQAr) of RMGV, and a total of 96 samplings were collected between the two sampling periods. Bythe characterization and quantification of VOC was possible to quantify the OFPapplying the scale ofmaximumincrementalreactivity (MIR) proposed by Carter (1994). The results indicatedthat the predominant group of VOCs in the RMGV is the organic acids, followed by alcohols and substituted aromatics. Among the VOCs with the greatest OFP, the undecane, toluene , ethylbenzene and m, p-xylene compounds are the most abundant in RMGV, presentingthe means of 0,855 μg m-3, 0,365 μg m-3, 0,259 μg m-3and0,289 μg m-3, respectively, on the period 05/16/2013 to 06/21/2013. The results also indicatedthat the BTEX group consisting of benzene, toluene, ethylbenzene and m,p-xylenes are belowof the limitsconsidered harmful to the health of the population in RMGV . The ozone formingpotential in RMGV calculated from all the precursorsVOC group was 22.55 μg m-3insummer period and 32.11 μg m-3in the winter period. The toluene and o-xylene compounds are responsible for approximately 37 % of all OFPproduced from precursors VOC group. The assessment of the VOC/NOxratio revealed that the overall value of thatratio inRMGV is approximately 1.71, indicating that the region has a VOC-limiting condition for the production of ozone. Therefore, the adoption of measures only toremove NOxfrom the atmosphere of RMGV could favor reactions between OH and VOC, forming radicals that enable regenerate NO2increasingthenet rate of ozone production in the region.